Citizen Report Card Surveys : A Note on the Concept and Methodology - Waglé, Swarnim; Singh, Janmejay; Shah, Parmesh (World Bank, Washington, DC, 2012)
This note provides a short summary of the concept and key phases involved in implementing a citizen report card (CRC) survey. CRCs are client feedback surveys that provide a quantitative measure of user perceptions on the quality, efficiency and adequacy of different public services. They have been applied to numerous contexts in different regions. Beyond the process of executing a survey, CRCs involve efforts at dissemination and institutionalization that make them effective instruments to exact public accountability.